2021
DOI: 10.3233/shti210147
|View full text |Cite
|
Sign up to set email alerts
|

Federated Deep Learning Architecture for Personalized Healthcare

Abstract: Using deep learning to advance personalized healthcare requires data about patients to be collected and aggregated from disparate sources that often span institutions and geographies. Researchers regularly come face-to-face with legitimate security and privacy policies that constrain access to these data. In this work, we present a vision for privacy-preserving federated neural network architectures that permit data to remain at a custodian’s institution while enabling the data to be discovered and used in neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Different receptive fields under different layers. [19] In addition to the most common convolution, there are empty convolution, upsampling, BatchNorm [21] SeparableConv [22]receptive field; Receptive field is not the only information factor that affects the accuracy. Receptive field is also affected by information such as network depth, width, residual connection, BatchNorm, etc.…”
Section: • Anchor Informationmentioning
confidence: 99%
“…Different receptive fields under different layers. [19] In addition to the most common convolution, there are empty convolution, upsampling, BatchNorm [21] SeparableConv [22]receptive field; Receptive field is not the only information factor that affects the accuracy. Receptive field is also affected by information such as network depth, width, residual connection, BatchNorm, etc.…”
Section: • Anchor Informationmentioning
confidence: 99%
“…Studies have consistently shown that FL models outperformed traditional single-institution ML architectures [148,[151][152][153][154][155][156] and may be comparable to models built via central learning (centralized database) [137,138,[143][144][145][146][147][148][149][150]. In some studies, the FL approach has even been shown to be superior to alternative collaborative learning methods [137,145].…”
Section: Federated Learningmentioning
confidence: 99%